Synthesis of some Quinazolin One Derivatives for Their Antimicrobial Activity - Askar, Firyal Weli; Mohammed, Hammed H; Abdalgane, Hadel A (Al-Nahrain Journal of Science, 2018)
A series of derivatives for compound 2-(4-chlorophenyl)-4H-benzo[d] [1,3] oxazin-4-one with different aromatic substitution were proved. The newly synthesized derivatives have been supported by spectral data FTIR and H1 NMR. All the synthesized compounds were screened for their antimicrobial activity and compared with drug Amoxicillin as reference.